A Feasibility study on local goat's milk soaps - Alcantara, Raymund (College of Engineering, 2005)
The idea of manufacturing beauty soaps was chosen due to the seemingly inexhaustible demand of Filipinos for beauty products especially for the ones, which offers more value for their money. Thus, the new venture analyzed in this study, ADD Manufacturing Laboratories, plans to invest on manufacturing beauty soaps containing locally produced goat's milk, which is highly valued as a natural moisturizer since ancient times. Although some imported goat's milk soaps are already available in the local market, the ones thart are locally produced are limited in supply. Moreover, most of these products are sold at high prices. Thus producing such beauty soaps a relatively cheaper price may result in greater market share. The main determinant of the beauty soap's demand is population along with economic performance, social demography, and consumer preference. Based on these factors, the target market was selected. Among alternatives, the target market segments selected for the beauty soap includes the women belonging to social classes C and D living in Metro Manila falling under ages 30-59. Since the main demand determinant for ADD's product is population. the target market size was estimated for the next five years using the results of the survey, which estimates the percentage of the market selected wiling to buy the product. In the study, the target market size was projected to be about 320,000-340,000 for the next five years. Survey results show that the average yearly consumption of the target buyers is eleven (11) 135g- soap bars. Thus the yearly volume demand for the goat's milk soap could be estimated by multiplying the target market's size by the consumption rate. A penetration price of 31.75 was decided as the unit price for ADD's beauty soap. Assuming a market share of about 35%, the demand for ADD's product was calculated by multiplying the yearly volume demand by the unit price and the estimated market share. Thus the annual demand in value sales was projected for 2006-2010 to be between P39M and P42M. By studying the target market, as well as the competition, placement and promotions strategies were also developed .ADDs Mfg Labs shall utilize a one to tow levels of intermediaries of wholesalers and retailers. On the other hand, the company shall promote its products through advertisements and sales promotions. A sales plan was also developed, which is proportional to the size of the population of the different areas in Metro Manila. The overall budget for the sales plan is 3% of the total sales while the budget advertising and promotions is about 10% to 30% depending on the year. More marketing efforts are planned during the first two years of business. As a result, the total marketing budget should be enormous during the first few years of the product. Thus, the total marketing budget ranges from P8.1 M to about P15.6 M. There are three ways in which beauty soaps could be produced: the semi-boiling, full-boiling, and the cold process. In choosing what method to be used, the output quality, complexity, cost, and speed were considered. The nature of the beauty soap, as well as the production requirements, is also considered. In the end, the cold process was chosen since it is the most appropriate method for making goat's milk soaps. Aside from the goat's milk, several raw materials are needed to produce the beauty soap. These include fatty acids, caustic soda, builders and fillers, among others. Coconut oil was chosen as the main fatty acid because of its abundance and its suitability with the cold process method. Other soap ingredients is not a problem since chemical suppliers are abundant. The supply of goat's milk is also not a problem since only a small amount is needed in the soap production. Only an amount of 0.1% by weight goat's milk is used in the soap mixture, which is a formulation that is already used. In choosing the suppliers of the required raw materials, the price, availability, and delivery policies were taken into consideration. The delivery terms of the suppliers affects the inventory space needed for the raw materials. As shown in the study, an inventory space for a two to six day supply of raw materials are needed per day. It also influences the amount of work-in process, as well as finished goods, inventory space is needed. The amount of work-in process inventory is determined by the distribution terms. In the study, it was shown that the space needed for the work-in process and the finish goods inventory should at least equivalent to a one-day production. Equipment and tooling requirements were identified based on the producit9on process. Since the production method is the cold process, equipment and tooling are kept relatively simple in design. Much of the required equipment could be fabricated in local machine shops such as the soap mixers, oil tanks, soap trays, and soap cutters. In general, the supply and availability of the equipment is not a problem. The capacity planned for the plant facilities is based on the maximum daily production requirement of 4,409 units. Allowances were also considered in the capacity plan. The number of equipment and tooling, the space requirements, and the human resources required were derived from the estimated production rates of these operating units in relation to the maximum production requirements. Basically, there are no spacial skills required of the workers especially since training would be provided. The number of workers required in the production area based on the capacity plan is eight(8). These workers are overseen by a foreman, who is handled by a production manager. A quality assurance officer is also required to inspect the products from time to time. In general, the production organization of ADD Mfg labs is not top-heavy, which thus facilitates interaction among employees.